PENGEMBANAN MEDIA PEMBELAJARAN BERBASIS KOMIK PADA MATA PELAJARAN IPA - Indah Parawangsa Umar; Mohamad Jahja; Ritin Uloli (Jurnal Pendidikan Fisika Undiksha, 2023)
This research uses Research and Development (R&D) research with a 4D development model developed by Thiagarajan which consists of 4 stages, namely: definition, design, development and deployment. The results of this study indicate that: 1) the validation results of the learning media are stated to be very valid, 2) in the practicality of learning it is determined from the percentage of learning implementation which consists of three meetings which reach 98.13% with a very good category and the response of teachers and students through the response questionnaire gave a positive response, and 3) the effectiveness of learning tools was determined through the activities of students who obtained a percentage of 89.33% with very good criteria in three meetings and the learning outcomes of students who obtained an N-gain value of 0.765 which included in the high N-gain criterion. Based on the results of this study, it can be concluded that comic-based learning media meets the valid, practical and effective criteria